2021
DOI: 10.1016/s1872-2067(20)63752-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient spinel iron-cobalt oxide/nitrogen-doped ordered mesoporous carbon catalyst for rechargeable zinc-air batteries

Abstract: A robust oxygen-related electrocatalyst, composed of spinel iron-cobalt oxide and nitrogen-doped ordered mesoporous carbon (NOMC), was developed for rechargeable metal-air batteries. Electrochemical tests revealed that the optimal catalyst Fe0.5Co/NOMC exhibits superior activity with a half-wave potential of 0.89 V (vs. reversible hydrogen electrode) for the oxygen reduction reaction and an overpotential of 0.31 V at 10 mA cm −2 for the oxygen evolution reaction. For demonstration, the catalyst was used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As shown in Figure b, the FeCo-MHs cathode gives a maximum power density as high as 319.7 mW cm –2 , which is far higher than that for Fe-CNTs (240.6 mW cm –2 ) and Co-CNTs (172.3 mW cm –2 ). Notably, ZAB with FeCo-MHs as cathode catalyst displayed an exceptional lifetime for charge/discharge cycles; under 10 mA cm –2 , the resulting ZAB could run for 2000 h (12 000 cycles) without noticeable voltage fading (Figure c), showcasing the advantageous long-term stability over other reported electrocatalysts (Figure d). ,,,, Specifically, the FeCo-MHs cathode displayed an initial charge/discharge voltage gap as narrow as ∼0.87 V, and the voltage gap after long-term cycling could still be retained at ∼0.95 V; in addition, under a large current density of 20 mA cm –2 , the ZAB could run for 500 h (3300 cycles) (Figure S31). As a proof-of-concept illustration, we assembled a circuit comprising two FeCo-MHs-based ZABs in series, powering four red-light-emitting diodes in parallel (Figure S32).…”
Section: Resultsmentioning
confidence: 90%
“…As shown in Figure b, the FeCo-MHs cathode gives a maximum power density as high as 319.7 mW cm –2 , which is far higher than that for Fe-CNTs (240.6 mW cm –2 ) and Co-CNTs (172.3 mW cm –2 ). Notably, ZAB with FeCo-MHs as cathode catalyst displayed an exceptional lifetime for charge/discharge cycles; under 10 mA cm –2 , the resulting ZAB could run for 2000 h (12 000 cycles) without noticeable voltage fading (Figure c), showcasing the advantageous long-term stability over other reported electrocatalysts (Figure d). ,,,, Specifically, the FeCo-MHs cathode displayed an initial charge/discharge voltage gap as narrow as ∼0.87 V, and the voltage gap after long-term cycling could still be retained at ∼0.95 V; in addition, under a large current density of 20 mA cm –2 , the ZAB could run for 500 h (3300 cycles) (Figure S31). As a proof-of-concept illustration, we assembled a circuit comprising two FeCo-MHs-based ZABs in series, powering four red-light-emitting diodes in parallel (Figure S32).…”
Section: Resultsmentioning
confidence: 90%
“…1b, exhibits two prominent peaks centered at 711.1 eV and 724.4 eV, which correspond to Fe 2p 1/2 and Fe 2p 3/2 . 32 It shows that Fe (II) is the main component of the V O -FeOOH sample, and it also shows that unsaturated coordination bonds are formed in the sample, respectively. Additionally, two satellite peaks centered at 718.1 eV and 732.8 eV are attributed to these respective Fe 2p peaks.…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 94%
“…To alleviate the metal aggregation, a unique Al 2 O 3 nanolayer confinement technique has been proposed to construct Co 3 O 4 in a carbon matrix by directly pyrolyzing Zn/Co-ZIFs (Zhu et al, 2018) Additionally, the performance of the ORR can be significantly enhanced by using the proper H 2 treatment temperature. In addition to single metal oxide, spinel iron-cobalt oxide was reported that encapsulated in nitrogen-doped ordered mesoporous carbon for rechargeable metal-air batteries, exhibiting excellent activity with a half-wave potential of 0.89 V (Wei et al, 2021). Based on recent studies, the improved ORR/OER activity may have been caused by multiple factors, including enhanced electrical conductivity, altered electronic structure, and modified crystal structure, which were all attributed to carbon-metal oxide composites.…”
Section: Carbon-metal Oxide Compositesmentioning
confidence: 99%